The Effect of Telemidwifery Counseling on Breastfeeding Self-efficacy in Primiparous Women during the COVID-19 Pandemic - Fatemeh Mohammadi; Nasim Bahrami; Zainab Alimoradi (Hamadan University of Medical Sciences, 2023)
Background and Objective: Introduction: The COVID-19 pandemic restricts face-to-face breastfeeding counseling. The present study aimed to investigate "the effect of telemidwifery counseling on breastfeeding self-efficacy of primiparous mothers during the COVID-19 pandemic". Materials and Methods: This randomized controlled trial was conducted on 122 primiparous pregnant mothers referring to health centers in Qazvin, Iran, from January to May 2022. Random allocation was done using the balanced blocks method. In addition to the usual counseling during prenatal care, the intervention group received virtual breastfeeding counseling individually on the social media platform during pregnancy. Breastfeeding self-efficacy, the mother's perception of breastfeeding adequacy, and the mother's breastfeeding status were investigated on the 5th, 15th, and 45th days after childbirth. Results: The mean breastfeeding self-efficacy score on the 5th day after childbirth between the intervention and control groups was not significantly different; however, the mean difference of this score (95% Confidence Interval) between the two groups on the 15th day equals 4.13 (1.41- 6.86) and on the 45th, day it was 6.62 (1.12- 4.41), which was significantly higher in the intervention group than the control group. There was no significant difference in the breastfeeding status of the mothers in the two groups during the follow-up period. The mean score of the mother's perception of breastfeeding adequacy in the intervention group was significantly higher than the control group only on the 45th day after delivery with a mean difference of 1.12 (0.53-1.71). Conclusion: Telemidwifery breastfeeding counseling can be suggested as an effective method to increase the breastfeeding self-efficacy of primiparous mothers.